Examining Inclusive Policies and Practices in the Nepal Police: A Case Study of Recruitment and Selection of Inspectors - Rai, Tika Ram (Journal of Business and Social Sciences Research, 2025)
This paper examines the implementation and practice of inclusive recruitment and selection policies within the Nepal Police by comparing three public recruitment cycles of police inspectors, identifying distinct models based on reservation quota implementation. The study followed a comparative and longitudinal research design to interpret the data. The 2009 ‘Spillover’ model succeeded by allowing reserved-category candidates to compete in the open category, ensuring high integration and filling quotas. Conversely, the 2013 ‘Rigid Quota’ model failed; by selecting open-category candidates first, it drained qualified candidates from reserved groups, leaving quotas unfilled despite sufficient applicants. The 2014 Precise and Protected’ model ensured all quotas were met, likely by using parallel selection processes that protected reserved seats from being drained. The findings demonstrate that administrative mechanisms, not applicant interest, are the critical determinant of reservation policy success. The study provides valuable insights that can assist the selection committee of the Public Service Commission of Nepal in effectively managing recruitment procedures, particularly those related to the Nepal Police.